If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -5 = 3x + -2(x + -3) Reorder the terms: -5 + 6x = 3x + -2(x + -3) Reorder the terms: -5 + 6x = 3x + -2(-3 + x) -5 + 6x = 3x + (-3 * -2 + x * -2) -5 + 6x = 3x + (6 + -2x) Reorder the terms: -5 + 6x = 6 + 3x + -2x Combine like terms: 3x + -2x = 1x -5 + 6x = 6 + 1x Solving -5 + 6x = 6 + 1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -5 + 6x + -1x = 6 + 1x + -1x Combine like terms: 6x + -1x = 5x -5 + 5x = 6 + 1x + -1x Combine like terms: 1x + -1x = 0 -5 + 5x = 6 + 0 -5 + 5x = 6 Add '5' to each side of the equation. -5 + 5 + 5x = 6 + 5 Combine like terms: -5 + 5 = 0 0 + 5x = 6 + 5 5x = 6 + 5 Combine like terms: 6 + 5 = 11 5x = 11 Divide each side by '5'. x = 2.2 Simplifying x = 2.2
| 25x+5=5x-1 | | 25x-.5=.5x-1 | | 4c*4d= | | 5x+(-135)=-60 | | 9x-4=51 | | 31-7x=5-3x-2(x-3) | | 20x^2-240x+3600=0 | | 6(3s+3)=72 | | 6x-8=60 | | 5xu+1=35 | | -3(2s-2)-6=-2(8s+2)-2 | | (y-6)/4=2 | | (1-5x)=5-2x | | |d+9|=-3 | | 3x+y=43 | | x9/2 | | (1+4x)-x(3-2x)= | | 5x-23/6=x-4 | | 12y-6y^2=0 | | 3x+3+2x-2+9x=180 | | 2(-2.2)-9(2(2.2)+5)=7(2(2.2)+3) | | 2x+2y-7y-4x=a | | -6-1/3w=0 | | 2(x-3)-4(3x-2)=12 | | 6x+2-11x=9-4x+2 | | 7x^4+6=y^2 | | 6(7x-4)=144 | | 18.75=0.3xtloge | | 6g+7=-5 | | 3a+8b+7a-6b= | | X11/5 | | 6y(6-y)=0 |